On the use of discounted cash flow method on the customer valuation - Portela, S.; Menezes, R. (International Journal of Latest Trends in Finance and Economics Sciences, 2011)
The Discounted Cash Flow Method has been widely argued as the best method to asset valuation. This article is about the valuation of customers. The use of historic customer profitability and the Discounted Cash Flow Method to customer valuation are discussed. Moreover, the components of customer lifetime value is presented and described.